2017
DOI: 10.1002/celc.201700901
|View full text |Cite
|
Sign up to set email alerts
|

Directed Growth of a Bimetallic MOF Membrane and the Derived NiCo Alloy@C/NixCo1‐xO/Ni Foam Composite as an Efficient Electrocatalyst for the Oxygen Evolution Reaction

Abstract: Hierarchically structured bimetallic NiCo‐MOF/LDH/Ni foam (NiCo‐MOF/LDH/NF; MOF=metal−organic framework, LDH=layered double hydroxides) composites were successfully fabricated by means of the in situ growth of NiCo‐MOF on the NiCo LDH buffer‐layer‐modified NF surface. After carbonization, the derived NiCo alloy@C/NixCo1‐xO/NF hierarchical nanocomposite showed excellent electrocatalytic activity with respect to the oxygen evolution reaction (OER); specifically, it exhibited a very low overpotential of 300 mV at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 32 publications
0
17
0
Order By: Relevance
“…Therefore, the synergy coupling of Co 3 O 4 nanocages and NiCo 2 O 4 nanosheets accounts for the high OER activity, similar to that in recent published works. 34,35 It is known that the OER activity of the electrode relies enormously upon the electrochemically active surface area (ECSA). Thus, C dl is calculated from the CV curve in the potential region of 0.00− 0.10 V without redox processes (Figure 6C and Figure S6).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the synergy coupling of Co 3 O 4 nanocages and NiCo 2 O 4 nanosheets accounts for the high OER activity, similar to that in recent published works. 34,35 It is known that the OER activity of the electrode relies enormously upon the electrochemically active surface area (ECSA). Thus, C dl is calculated from the CV curve in the potential region of 0.00− 0.10 V without redox processes (Figure 6C and Figure S6).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Recently, Tang et al reported a Co 3 O 4 @N-doped carbon bifunctional catalyst for overall water splitting, constructed from a ZIF@LDH precursor on Ni foam 34. Moreover, NiCo alloy@C/Ni x Co 1−x O/Ni foam hierarchical nanocomposite has been synthesized through an in situ growth of NiCo-MOF on the NiCo-LDH layer-modified Ni foam surface; the hybrid composites exhibit outstanding OER activity 35. However, there are very few reports on the fabrication of Co 3 O 4 /NiCo 2 O 4 /Ni foam composite used as an electrode material for OER.…”
mentioning
confidence: 99%
“…Layered double hydroxide (LDH), which is representative of inorganic pillared clays, has shown promising applications in catalysis, [7] adsorption, [8] anticorrosion, [9] and membrane separation [10] . Moreover, our recent study indicated that LDH‐based buffer layers could serve as competent heterogenous nucleation center facilitating in situ growth of a series of well‐intergrown metal‐organic framework (MOF) membranes (including ZIF‐7, [11] ZIF‐8, [12] ZIF‐67, [13] and HKUST‐1 [14] ), relying on their rich surface functionality and flexible chemical composition. Very recently, this approach was also proven effective in preparation of well‐intergrown COF (e.g., COF‐LZU1) membranes with excellent gas separation performances [15] …”
Section: Figurementioning
confidence: 99%
“…The material exhibited a 95 mV HER overpotential (η 10 ) in acidic medium, which is lower than other controlled materials, and it showed good stability in an acidic medium (Figure f,g). The formation of NiCo‐ZIF/LDH/NF by using NiCo LDH/NF as a starting material followed by a reaction with 2‐MeIm was reported . Finally, the material was converted to NiCo@C/Ni x Co 1–x O/NF under heating at 600 °C for 2 h in the presence of nitrogen flow.…”
Section: Energy Conversion and Storagementioning
confidence: 99%